2011
DOI: 10.1038/labinvest.2011.41
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with pravastatin attenuates progression of chronic pancreatitis in rat

Abstract: As appropriate therapies for pancreatic fibrosis and inflammation are limited, prognosis of chronic pancreatitis has not improved to date. Recent studies have shown that statins improve inflammation and fibrosis in several organs. We therefore examined the therapeutic effect of pravastatin on progression of chronic pancreatitis by starting this treatment after induction of pancreatic fibrosis in rats. Chronic pancreatitis was induced by continuous pancreatic ductal hypertension (PDH) for 14 days according to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…A splenic portion of pancreatic tissue was removed immediately after sacrifice and rinsed with ice-cold saline. The tissue samples were fixed in 4 % buffered neutral paraformaldehyde solution overnight, embedded in paraffin, and deparaffinized using standard procedures [ 20 , 21 ]. Thin Sections (5 µm) were dewaxed, dehydrated in a graded series of ethanol, and rehydrated, then stained with H&E for light microscopic examination (Leica, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…A splenic portion of pancreatic tissue was removed immediately after sacrifice and rinsed with ice-cold saline. The tissue samples were fixed in 4 % buffered neutral paraformaldehyde solution overnight, embedded in paraffin, and deparaffinized using standard procedures [ 20 , 21 ]. Thin Sections (5 µm) were dewaxed, dehydrated in a graded series of ethanol, and rehydrated, then stained with H&E for light microscopic examination (Leica, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Only 12 reports of statin-induced pancreatitis have been reported [34]. More recent studies have demonstrated that statins may actually have a protective role for CP, attenuating inflammation and fibrosis, most likely due to their antioxidative properties [35].…”
Section: Discussionmentioning
confidence: 99%
“…6,49 Furthermore, studies conducted in animal models suggest that statin therapy may be beneficial in both established acute pancreatitis and chronic pancreatitis. [50][51][52] Major guidelines of lipid-modifying therapy such as the National Cholesterol Education Program Third Report of the Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults (NCEP ATP III) 8 and the NationalInstituteforHealthandClinicalExcellence (NICE) Type 2 Diabetes guideline 9 suggesttheadditionoffibratetherapy in patients with moderately elevated triglyceride levels and above (Ͼ400 mg/dL and Ͼ500 mg/dL, respectively). This is based on the rationale that hypertriglyceridemiaisawell-recognizedcauseofpancreatitis and that lowering of triglyceride levels should be clinically beneficial.…”
Section: Commentmentioning
confidence: 99%
“…Studies showing associations between statin use and both a reduction in bile cholesterol and reduced risk of gallstones on statins suggest the possibility of a protective effect (6;49). Furthermore, studies conducted in animal models suggest the possibility that statin therapy may be associated with benefit for both acute pancreatitis and chronic pancreatitis (50)(51)(52). suggest that fibrate therapy should be prescribed for patients with moderately elevated triglyceride levels and higher (>500mg/dL and >400mg/dL respectively).…”
Section: Commentmentioning
confidence: 99%